Enzymatic clarification of guyabano wine - Garrovillo, Ruby Bernadette D.
The study was divided into three phases: 1) Proximate analysis of the guayabano fruit and the determination of the clarifying activity of pectinase; 2) Fermentation of wine clarified with pectinase at different stages of fermentation; 30 Objective and subjective analysis of the clarified guayabano wines. In Phase I, the clarifying activity of pectinase was measured by optical transmittance. Result showed that the pectinase gave a 70% clarifying activity in guayabano extract. In Phase II, the result showed that the wine clarified with pectinase during fermentation significantly increased in titratable acidity and rapidly decreased in soluble solid content as compared to the pre-fermentation clarified wine, post-fermentation clarified wine, and the control. In Phase III, the wine treated with pectinase during fermentation had the lowest absorbance or the highest transmittance as compared to the other treatments. This indicated that the pectinase was more effective in clarifying wines if it was utilized during fermentation. Furthermore, statistical analysis showed that the said treatment was not preferred. Among the four treatments, the post-fermentation clarified wine was the most preferred.